Skip to content

Commit 221ea0e

Browse files
committed
[ lecture-notes ] Week04Solutions
1 parent d05203a commit 221ea0e

File tree

2 files changed

+294
-1
lines changed

2 files changed

+294
-1
lines changed

README.md

+1-1
Original file line numberDiff line numberDiff line change
@@ -52,7 +52,7 @@ The notes are Haskell files with interleaved code and commentary. You are encour
5252
- [Tutorial Solutions](lecture-notes/Week03Solutions.hs)
5353
- [Week 4](lecture-notes/Week04.hs) : Patterns of Recursion
5454
- [Tutorial Problems](lecture-notes/Week04Problems.hs)
55-
<!-- - [Tutorial Solutions](lecture-notes/Week04Solutions.hs) --->
55+
- [Tutorial Solutions](lecture-notes/Week04Solutions.hs)
5656
- [Week 5](lecture-notes/Week05.hs) : Classes of Types
5757
- [Tutorial Problems](lecture-notes/Week05Problems.hs)
5858
<!-- - [Tutorial Solutions](lecture-notes/Week05Solutions.hs) -->

lecture-notes/Week04Solutions.hs

+293
Original file line numberDiff line numberDiff line change
@@ -0,0 +1,293 @@
1+
{-# LANGUAGE ParallelListComp #-}
2+
{-# OPTIONS_GHC -fwarn-incomplete-patterns #-}
3+
module Week04Solutions where
4+
5+
import Prelude hiding (foldr, foldl, Maybe (..), Left, Right, filter, zip, map, concat)
6+
import Data.List.Split (splitOn)
7+
import Data.List hiding (foldr, foldl, filter, map, concat)
8+
import Week04
9+
10+
{------------------------------------------------------------------------------}
11+
{- TUTORIAL QUESTIONS -}
12+
{------------------------------------------------------------------------------}
13+
14+
{- 1. The following recursive function returns the list it is given as
15+
input: -}
16+
17+
listIdentity :: [a] -> [a]
18+
listIdentity [] = []
19+
listIdentity (x:xs) = x : listIdentity xs
20+
21+
{- Write this function as a 'foldr': -}
22+
23+
listIdentity' :: [a] -> [a]
24+
listIdentity' = foldr (\x r -> x : r) -- step case, combines the head and the tail using ':'
25+
[] -- base case, the empty list []
26+
27+
{- See how the base case is the same as the first clause in the original
28+
definition of 'listIdentity'. The step case is the same as the
29+
second clause, except that the recursive call 'listIdentity xs' has
30+
been replaced by 'r'.
31+
32+
We can also shorten this to:
33+
34+
listIdentity' = foldr (:) []
35+
36+
because '(:)' is the same thing as '(\x r -> x : r)': any infix
37+
operation, like ':' can be written as a function that takes two
38+
arguments by putting it in brackets.
39+
40+
Let's see how this works by writing out the steps on a short list:
41+
42+
foldr (\x r -> x:r) [] [1,2]
43+
= (\x r -> x:r) 1 (foldr (\x r -> x:r) [] [2])
44+
= (\x r -> x:r) 1 ((\x r -> x:r) 2 (foldr (\x r -> x:r) [] []))
45+
= (\x r -> x:r) 1 ((\x r -> x:r) 2 [])
46+
= (\x r -> x:r) 1 (2:[])
47+
= 1:2:[]
48+
= [1,2]
49+
-}
50+
51+
{- 2. The following recursive function does a map and a filter at the
52+
same time. If the function argument sends an element to
53+
'Nothing' it is discarded, and if it sends it to 'Just b' then
54+
'b' is placed in the output list. -}
55+
56+
mapFilter :: (a -> Maybe b) -> [a] -> [b]
57+
mapFilter f [] = []
58+
mapFilter f (x:xs) = case f x of
59+
Nothing -> mapFilter f xs
60+
Just b -> b : mapFilter f xs
61+
62+
{- Write this function as a 'foldr': -}
63+
64+
mapFilter' :: (a -> Maybe b) -> [a] -> [b]
65+
mapFilter' f = foldr (\x r -> case f x of Nothing -> r -- \___ step case
66+
Just b -> b : r) -- /
67+
[] -- base case
68+
69+
{- The base case is the same as for 'listIdentity'' above.
70+
71+
In the step case, we have to decide whether or not to add the new
72+
element to the list. We 'case' on the result of 'f x'. If it is
73+
'Nothing', we return 'r' (which is representing the recursive call
74+
'mapFilter f xs'). If it is 'Just b', we put 'b' on the front of
75+
'r' (compare the 'listIdentity' function above). -}
76+
77+
78+
{- 3. Above we saw that 'foldl' and 'foldr' in general give different
79+
answers. However, it is possible to define 'foldl' just by using
80+
'foldr'.
81+
82+
First try to define a function that is the same as 'foldl',
83+
using 'foldr', 'reverse' and a '\' function: -}
84+
85+
{- The key thing to notice is that the difference between 'foldl' and
86+
'foldr' is that 'foldl' goes left-to-right and 'foldr' goes right
87+
to left. So it makes sense to reverse the input list. The function
88+
argument 'f' then takes its arguments in the wrong order, so we
89+
flip them using a little '\' function. -}
90+
91+
foldlFromFoldrAndReverse :: (b -> a -> b) -> b -> [a] -> b
92+
foldlFromFoldrAndReverse f x xs = foldr (\a b -> f b a) x (reverse xs)
93+
94+
{- We could have also used the 'flip' function from last week's
95+
questions, which is provided by the standard library: -}
96+
97+
foldlFromFoldrAndReverse_v2 :: (b -> a -> b) -> b -> [a] -> b
98+
foldlFromFoldrAndReverse_v2 f x xs = foldr (flip f) x (reverse xs)
99+
100+
{- Much harder: define 'foldl' just using 'foldr' and a '\' function: -}
101+
102+
{-
103+
foldl :: (b -> a -> b) -> b -> [a] -> b
104+
foldl f a [] = a
105+
foldl f a (x:xs) = foldl f (f a x) xs
106+
-}
107+
108+
-- This is quite a bit more complex than the other solution using
109+
-- 'reverse'. The key idea is to construct a "transformer" function
110+
-- with 'foldr' that acts like 'foldl' would. Try writing out some
111+
-- steps of this function with some example 'f's to see how it works.
112+
113+
foldlFromFoldr :: (b -> a -> b) -> b -> [a] -> b
114+
foldlFromFoldr f a xs = foldr (\a g b -> g (f b a)) id xs a
115+
116+
{- Remember from Week03 that 'id' is '\x -> x': the function that just
117+
returns its argument. -}
118+
119+
{- Understanding 'foldlFromFoldr' may take a bit of work. The key point
120+
is that we use 'foldr' to build a /function/ from the input list
121+
'xs' that will compute the left fold from any given initial value.
122+
123+
In more detail, the 'foldr' is used to build a function that takes
124+
an accumulator argument, similar to the 'fastReverse' function in
125+
Week01:
126+
127+
- The 'id' is the base case: it takes the accumulator and returns
128+
it (compare the first clause of 'foldl', which returns 'a').
129+
130+
- The '\a g b -> g (f b a)' is the step case:
131+
132+
- 'a' is the value from the input list
133+
- 'g' is the result of processing the rest of the list, which a
134+
/function/ that is expecting an accumulator.
135+
- 'b' is the accumulator so far.
136+
137+
So this function combines the value 'a' and the accumulator 'b'
138+
using 'f', and passes that to 'g'.
139+
140+
So it is doing a 'fastReverse' and a 'foldr' at the same time (with
141+
the flipped arguments to 'f'), so can be seen as an optimised
142+
version of the first solution.
143+
144+
It may be helpful to understand the /types/ involved. We are
145+
writing a function with this type (the type of 'foldl'):
146+
147+
(b -> a -> b) -> b -> [a] -> b
148+
149+
and 'foldr' has this generic type:
150+
151+
(a -> b -> b) -> b -> [a] -> b
152+
153+
but we are *using* 'foldr' with this type:
154+
155+
foldr :: (a -> (b -> b) -> (b -> b)) -> -- 'step case'
156+
(b -> b) -> -- 'base case'
157+
[a] -> -- 'input list'
158+
b -> -- 'initial accumulator'
159+
b -- result
160+
161+
Note that the 'step case' takes a function and returns a function:
162+
we are building a /function/ by recursion.
163+
164+
Don't worry if you don't get this at the first few attempts. It
165+
takes some time to rewrite your mind to see functions as something
166+
that can be built incrementally by other functions! Looking at the
167+
types is usually a good way to not get lost. -}
168+
169+
170+
171+
{- 4. The following is a datatype of Natural Numbers (whole numbers
172+
greater than or equal to zero), represented in unary. A natural
173+
number 'n' is represented as 'n' applications of 'Succ' to
174+
'Zero'. So '2' is 'Succ (Succ Zero)'. Using the same recipe we
175+
used above for 'Tree's and 'Maybe's, work out the type and
176+
implementation of a 'fold' function for 'Nat's. -}
177+
178+
data Nat
179+
= Zero -- a bit like []
180+
| Succ Nat -- a bit like x : xs, but without the 'x'
181+
deriving Show
182+
183+
foldNat :: (b -> b) -> b -> Nat -> b
184+
foldNat succ zero Zero = zero
185+
foldNat succ zero (Succ n) = succ (foldNat succ zero n)
186+
187+
{- HINT: think about proofs by induction. A proof by induction has a
188+
base case and a step case. -}
189+
190+
{- Here we have 'zero' for the base case, 'succ' for the step case.
191+
192+
As an example, we can define 'add' for 'Nat' in terms of 'foldNat',
193+
which has a similar structure to 'append' for lists: -}
194+
195+
add :: Nat -> Nat -> Nat
196+
add x y = foldNat Succ y x
197+
198+
{- 5. Write a list comprehension to generate all the cubes (x*x*x) of
199+
the numbers 1 to 10: -}
200+
201+
cubes :: [Int]
202+
cubes = [ x*x*x | x <- [1..10] ]
203+
204+
205+
{- 6. The replicate function copies a single value a fixed number of
206+
times:
207+
208+
> replicate 5 'x'
209+
"xxxxx"
210+
211+
Write a version of replicate using a list comprehension: -}
212+
213+
replicate' :: Int -> a -> [a]
214+
replicate' n a = [ a | _ <- [1..n]]
215+
216+
{- 7. One-pass Average.
217+
218+
It is possible to use 'foldr' to
219+
implement many other interesting functions on lists. For example
220+
'sum' and 'len': -}
221+
222+
sumDoubles :: [Double] -> Double
223+
sumDoubles = foldr (\x sum -> x + sum) 0
224+
225+
lenList :: [a] -> Integer
226+
lenList = foldr (\_ l -> l + 1) 0
227+
228+
{- Putting these together, we can implement 'avg' to compute the average
229+
(mean) of a list of numbers: -}
230+
231+
avg :: [Double] -> Double
232+
avg xs = sumDoubles xs / fromInteger (lenList xs)
233+
234+
{- Neat as this function is, it is not as efficient as it could be. It
235+
traverses the input list twice: once to compute the sum, and then
236+
again to compute the length. It would be better if we had a single
237+
pass that computed the sum and length simultaneously and returned a
238+
pair.
239+
240+
Implement such a function, using foldr: -}
241+
242+
sumAndLen :: [Double] -> (Double, Integer)
243+
sumAndLen = foldr (\x (sum, len) -> (x + sum, len + 1)) (0,0)
244+
245+
-- NOTE: The solution combines the functions used in 'sumDoubles' and
246+
-- 'lenList' by making it take a pair '(sum,len)' as well as the list
247+
-- element 'x'. It then adds 'x' to the 'sum' part and '1' to the
248+
-- 'len' part.
249+
250+
{- Once you have implemented your 'sumAndLen' function, this alternative
251+
average function will work: -}
252+
253+
avg' :: [Double] -> Double
254+
avg' xs = total / fromInteger length
255+
where (total, length) = sumAndLen xs
256+
257+
{- 8. mapTree from foldTree
258+
259+
Here is the 'Tree' datatype that is imported from the Week04 module:
260+
261+
data Tree a
262+
= Leaf
263+
| Node (Tree a) a (Tree a)
264+
deriving Show
265+
266+
As we saw in the lecture notes, it is possible to write a generic
267+
recursor pattern for trees, similar to 'foldr', copied here for reference:
268+
269+
foldTree :: b -> (b -> a -> b -> b) -> Tree a -> b
270+
foldTree l n Leaf = l
271+
foldTree l n (Node lt x rt) = n (foldTree l n lt) x (foldTree l n rt)
272+
273+
Your job is to implement 'mapTree' (from Week03) in terms of
274+
'foldTree': -}
275+
276+
mapTree :: (a -> b) -> Tree a -> Tree b
277+
mapTree f = foldTree Leaf -- Leaf case: 'Leaf's become 'Leaf's
278+
(\l x r -> Node l (f x) r) -- Node case: 'Node's become 'Node's, but with the data changed
279+
280+
{- Here is the explicitly recursive version of 'mapTree', for
281+
reference: -}
282+
283+
mapTree0 :: (a -> b) -> Tree a -> Tree b
284+
mapTree0 f Leaf = Leaf
285+
mapTree0 f (Node lt x rt) = Node (mapTree0 f lt) (f x) (mapTree0 f rt)
286+
287+
288+
{- 9. Finally, use 'foldTree' to flatten a tree to list in left-to-right
289+
order: -}
290+
291+
flatten :: Tree a -> [a]
292+
flatten = foldTree [] -- Leaf case: has no elements, so is the empty list
293+
(\l x r -> l ++ [x] ++ r) -- Node case: append the left, middle, and right together

0 commit comments

Comments
 (0)